M.A.K. Halliday’s Actualization of linguistic flows in text-based BIPA Learning - Rahmawati, Ida Yeni; Santoso, Anang; Taufiqurrahman, Febri; Hyink, Sean (Jurnal Pendidikan Edutama, 2024)
BIPA teaching today uses a text-based approach as an approach that is believed to be able to help students understand Indonesian language texts. This study aims to explain the actualization of M.A.K.Halliday's linguistic flow in text-based BIPA learning. Qualitative descriptive is a research method used with a content analysis approach. The data for this research were obtained from document data and literature studies. Based on an in-depth analysis, seven types of language functions were found according to Halliday's theory, which are contained in the book My Best Friend Indonesia BIPA. The language functions are (1) informational, (2) directive, (3) contextual, (4) interactional, (5) expressive, (6) poetic, and (7) metalingual. Thus, the book Sahabatku BIPA 7 contains seven language function values, which are in line with Halliday's views in Systemic Functional Linguistics (LFS).